Epidemiology and Risk Factors of Dengue Fever Outbreak in Peshawar, Pakistan: A Hospital-Based Surveillance Study - Ullah, Wasia; Izaz, Muhammad; Nasir, Abdul; Miss, Rabia; Ziaul Islam; Khan, Muhsin; Rafi Ullah; Maula, Fazal (Indus Journal of Bioscience Research, 2025)
Dengue fever remains a major public health concern in tropical areas, with recurrent outbreaks in Pakistan’s cities. This study investigates the epidemiology and risk factors associated with the 2022 dengue outbreak in Peshawar District, Khyber Pakhtunkhwa. A total of 9,490 laboratory-confirmed cases were analyzed from four major hospitals from June 2022 to December 2022, making this one of the region’s largest documented outbreaks. The outbreak followed distinct temporal patterns, with peak transmission occurring during the 40th epidemiological week (8-14 October; n=1,288 cases), which coincided with post-monsoon conditions. Town 3 was identified as the epicenter (37.2% of cases), with significant clustering in slum areas (OR = 2.1, 95% CI: 1.8-2.4, p < 0.001). Demographic study found a greater occurrence among males (68.2%) and young individuals aged 20-29 years (27.1%), indicating occupational and behavioral exposure risks. The case fatality rate remained low (0.031%), indicating better clinical treatment than in earlier epidemics. Environmental factors such as uncovered water storage (76.0%; OR=3.4, p<0.001) and prolonged water storage >24 hours (92.0%; OR=5.2, p<0.001), as well as behavioral factors such as non-use of mosquito nets (93.0%; OR=6.3, p<0.001) and sleeping outdoors (44.0%; OR=2.8, p<0.001), were identified as critical risk factors. Travel history was documented in 61.5% of cases, emphasizing human mobility as an important transmission factor. The findings highlight the intricate interaction of meteorological, infrastructural, and social behavioral variables influencing dengue spread in urban Pakistan. This study provides evidence for targeted treatments, highlighting the need for integrated vector control techniques, better water infrastructure, and community-based awareness campaigns to reduce future epidemics in high-risk urban settings.